Rancang Bangun Pembangkit Nanohidro Untuk Keperluan Darurat Di Alam Terbuka - Agus Supardi (Universitas Negeri Padang, 2019)
Currently various outdoor activities are carried out by the community. These activities are sometimes carried out for several days. To support these activities, emergency power sources are needed to recharge the batteries for lighting, communication equipment and other electronic equipment. Emergency power sources used by many people are powerbank with a limited capacity. If the outdoor activities are carried out for several days, the powerbank will not be sufficient to meet the needs. Therefore, a small scale power plant is needed by utilizing the existing natural resources such as water flow or wind. This research aims to design and to make a prototype of a nanohydro power plant that can be used to meet electrical energy needs during outdoor activities. The research begins with designing a nanohydro power plant system includes a water turbine, mini generator, and battery charger. After that, the generator prototype was made. The prototype was tested in the laboratory and on the river. Tests are carried out in no-load and loaded conditions. In each test, a voltage measurement is carried out on the generating system. The laboratory test results show that the mini generator can generate voltage from 0.57 - 6.40 V when rotated at speeds of 150 - 3000 rpm. When tested in a river with water velocity varying from 0.25 to 0.45 m/s, the generator can generate a voltage of 1.9 - 3.1 V.